Exploring the Modulatory Effects of Vitamin B12 on Morphine-Induced Conditioned Place Preference in Rats - Uskur, Tugce; Tasdemir, Fatma Unlu; Ozturk, Mehmetaykut; Sonmez, Haktan; Seven, Zeynep Gizem Todurga; Gokdemir, Selim; Bastan, Burak; Faikoglu, Gokhan; Faikoglu, Kuebra Saygisever; Ozyazgan, Sibel; Yillar, Duendar Okan; Akkan, Ahmet Gokhan (AVES, 2025)
Background: This study aims to investigate the effects of vitamin B12 on morphine-induced conditioned place preference (CPP), a model commonly used to assess the rewarding effects of drugs. Morphine is a potent analgesic widely used for moderate to severe pain, but it also poses a significant risk of addiction. Previous studies suggest that cyanocobalamin (vitamin B12) may enhance the analgesic effects of morphine and reduce tolerance, but its impact on morphine addiction remains unclear. Methods: The experiment followed phases of habituation, pre-conditioning, conditioning, and post-conditioning. Adult male Wistar albino rats (250-300 g) were randomly divided into 3 groups (n = 8 per group): control (saline), morphine (10 mg/kg), and a combination group of vitamin B12 (2 mg/kg) with morphine. The effects of saline, morphine, and the morphine-vitamin B12 combination on CPP were assessed. All drugs and saline were administered intraperitoneally (ip). Results: Morphine (10 mg/kg) significantly induced CPP compared to the saline group (P < .0001). Vitamin B12 (2 mg/kg) did not produce a statistically significant difference in morphine-induced CPP compared to the control group. Conclusion: Morphine induces a significant place preference, and vitamin B12 did not produce a statistically significant difference in reducing this effect. Further research with different doses of vitamin B12 is necessary to fully investigate these effects.
Keywords: CYANOCOBALAMIN VITAMIN-B12; TOLERANCE; INVOLVEMENT; DEPENDENCE; EXPRESSION; PAIN; Pharmacology & Pharmacy; Psychiatry